IMPROVE THE ABILITY TO RECOGNIZE NUMBERS THROUGH DICE GAMES IN GROUP A PAUD TERPADU QATHRUN NADA BANJARMASIN - Nufus, Hayatun (E-CHIEF Journal, 2023)
The background of this research was the low cognitive abilities of children in recognizing numbers. This problem was caused by a lack of varied media and methods, the use of media tools and learning resources, as well as less engaging teaching strategies by teachers/educators. This study aimed to describe the teacher’s activities, children’s activities, and analyze the learning outcomes of children’s cognitive abilities in recognizing numbers through dice games in Group A of Integrated Early Childhood Education Qathrun Nada Banjarmasin. This research used Classroom Action Research (CAR) conducted in two cycles with 6 male and 6 female subjects in Group A of Integrated Early Childhood Education Qathrun Nada Banjarmasin. Data were obtained through observation, documentation, and data analysis. Based on the activities conducted, teacher activities increased from the “Good” category to the “Very Good” category, children’s activities increased from a score of 63% to a score of 100%, and children’s learning outcomes increased from the “Sufficient” category to the “Very Good” category. The research concluded that teacher activities, children’s activities, and children’s ability to recognize numbers increased from Cycle I to Cycle II. The results of this study could be used as a reference for selecting models in introducing numbers in the cognitive aspects of children